Isolation of a fully infectious variant of parvovirus H-1 supplanting the standard strain in human cells. - Faisst, S (1995)
A variant H-1 virus, designated H-1 dr virus, was isolated from stock of the standard H-1 virus strain propagated in the newborn human kidney cell line NB-E. Molecular cloning and sequence analysis revealed an in-frame deletion at map positions 39 to 41. This deletion affects the open reading frames encoding the nonstructural proteins NS-1 and NS-2 and the untranslated leader sequence of the R3 transcripts encoding the capsid proteins. In addition, H-1 dr virus harbors a 58-nucleotide duplication inboard from the right-hand terminal palindrome. Internal deletions and terminal reiterations are hallmarks of H-1 virus type I variants that typically are defective interfering particles. Indeed, H-1 dr virus was found to progressively supplant the standard strain in serially coinfected NB-E cell cultures. However, H-1 dr virus differed from previously described type I variants in its full infectivity, as was apparent from its ability to give yields of replication and progeny virus production that were similar to those of the standard virus strain in NB-E cells. Hence, the interference of H-1 dr virus in the propagation of standard H-1 virus in coinfected cells was not accompanied by a drop in the titer of infectious virus. Moreover, H-1 dr virus proved to induce the same pathogenic effects in newborn hamsters as the standard virus strain did.